Commercial air travel in Argentina: representations and experiences, 1929-1958 - Melina Piglia (Avances del Cesor, 2015)
This work explores the construction of air travel as a practice of consumption in Argentina before the implementation of the jet. First, it addresses the material aspects of air passenger transport, focusing on the development of the aircraft, and, how it led a sharp increase of seats per kilometer and, in turn, a growth of the number of passengers. Then, the work explores the air travel, looking at embodied practices of travelling triggered by the novel experience of flying; it also discusses how this practice was transforming over time and focuses on norms and disciplinary practices which shaped people behaviors creating a new kind of passenger: the air traveler. Finally, the paper examines the emergence of social representations about air travel as a safe, desirable, modern, exciting, and distinguished travel creating a broad social acceptance of aviation, named at that time as “aviation awareness”, among those who could and could not experience the air.